2001
DOI: 10.1016/s0735-1097(01)01403-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of right ventricular monomorphic extrasystoles

Abstract: In this long-term follow-up study, no patient died of sudden death nor developed ARVD; two-thirds of the patients were asymptomatic, and, in half of the patients, ectopy had disappeared. Focal fatty replacement in the right ventricle was present in most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 18 publications
3
96
1
4
Order By: Relevance
“…One issue would be the fact that the RVOT-PVC had been spontaneously suppressed. Gaita et al 19 conducted a longitudinal study in 61 patients with RVOT-PVC and observed that the symptoms disappeared spontaneously in two-thirds of patients for an average period of 15 years. However, one third of the patients persisted with RVOT-PVC and continued symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…One issue would be the fact that the RVOT-PVC had been spontaneously suppressed. Gaita et al 19 conducted a longitudinal study in 61 patients with RVOT-PVC and observed that the symptoms disappeared spontaneously in two-thirds of patients for an average period of 15 years. However, one third of the patients persisted with RVOT-PVC and continued symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent premature ventricular complexes (PVCs) are one of the major causes of reversible cardiomyopathy [1][2][3]. Tachycardia induced cardiomyopathy belongs to the acquired dilative cardiomyopathies and requires exclusion of other underlying disorders and observation of left ventricle (LV) functional improvement after achievement of arrhythmia control for diagnosis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic PVCs in patients without structural heart disease (SHD) are usually considered benign [1][2][3]. Successful elimination of the PVCs, either by radiofrequency (RF), catheter ablation, or antiarrhythmic drugs, may improve or even normalise LV systolic function [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] In contrast, it has been reported that a small number of patients develop polymorphic VT and /or VF, thereby suggesting the malignant entity. [12,13,[18][19][20] There are several studies attempting to differentiate such a malignant form of RVOT-VT from a benign one.…”
Section: Discussionmentioning
confidence: 99%